(untitled) (Baghdad Science Journal, 2022)
Thin films of ZnO nano crystalline doped with different concentrations (0, 6, 9, 12, and 18 )wt. % of copper were deposited on a glass substrate via pulsed laser deposition method (PLD). The properties of ZnO: Cu thin-nanofilms have been studied by absorbing UV-VIS, X-ray diffraction (XRD) and atomic force microscopes (AFM). UV-VIS spectroscopy was used to determine the type and value of the optical energy gap, while X-ray diffraction was used to examine the structure and determine the size of the crystals. Atomic force microscopes were used to study the surface formation of precipitated materials. The UV-VIS spectroscopy was used to determine the type and value of the optical energy gap.